2013
DOI: 10.1016/j.meatsci.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pregnancy and feeding level on carcass and meat quality traits of Nellore cows

Abstract: Carcass and meat quality traits of 16 pregnant and 5 non-pregnant cows fed at 1.2 times maintenance and 16 pregnant and 6 non-pregnant fed ad libitum were evaluated. Pregnancy did not affect final body weight (FBW; P=0.0923), cold carcass yield (CCY; P=0.0513), longissimus muscle area (LMA; P=0.8260), rib fat thickness (RFT; P=0.1873) and shear force (WBSF; P=0.9707). A lower FBW (P=0.0028), LMA (P=0.0048) and RFT (P=0.0001) were observed in feed restricted cows. However, no differences were found for CCY (P=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The effects of diet and animal type on flavor and juiciness have been assessed in a few studies. Duarte et al [7] have shown, in Nellore cattle, that juiciness and flavor are less affected by the finishing diet and have a negative correlation to growth rate. Finishing diets leading to high fat deposition (and low growth rate), such as a long fattening period with a low energy level diet, may increase juiciness and flavor intensity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of diet and animal type on flavor and juiciness have been assessed in a few studies. Duarte et al [7] have shown, in Nellore cattle, that juiciness and flavor are less affected by the finishing diet and have a negative correlation to growth rate. Finishing diets leading to high fat deposition (and low growth rate), such as a long fattening period with a low energy level diet, may increase juiciness and flavor intensity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…During the early phase of organogenesis, several animal studies indicated the importance of maternal nutrition for fetal stage-critical events regarding gastrointestinal tract development including expansion, differentiation and vascularization. Fetuses from dams subjected to nutrient restriction during early to mid-gestation have decreased growth of the gastrointestinal tract, including liver (Duarte et al, 2013;Wang et al, 2008). In humans, maternal dietary amino acid supplementation to improve fetal growth has been considered as an option to prevent or treat intrauterine growth restriction, as the specific amino acid transport system can transfer all of the BCAAs (Brown et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine multiparous Nellore cows with average initial body weight of 451 ± 10 kg, age of 5.6 ± 0.5 years and body condition score of 4.4 ± 0.2 (1 to 9 scale) were used. Cattle used in the present study were from an experiment reported by Duarte et al [ 15 ]. From the initial 49 cows, 32 were randomly separated and hand mated with Nellore bulls to form the pregnant group.…”
Section: Methodsmentioning
confidence: 99%